THEORIZING CHANGE: THE ROLE OF PROFESSIONAL ASSOCIATIONS IN THE TRANSFORMATION OF INSTITUTIONALIZED FIELDS. - Greenwood, R.; Hinings, C. R.; Suddaby, R. (Academy of Management Journal, 2002)
This study examines the role of professional associations in a changing, highly institutionalized organizational field and suggests that they play a significant role in legitimating change. A model...